Fostering Students’ Pronunciation of /ð/ and /θ/ Sounds by Utilising Tongue Twister - Bayu, Andi Muhammad; Mustafa , Mutakhirani (Elsya : Journal of English Language Studies, 2019)
The objective of this research is to find out whether or not the improvement of the students’ pronunciation skill of /ð/ and /θ/ sounds, the population of the research was the third semester of English Education Department of Universitas Muhammadiyah Bulukumba in academic year of 2018/2019 consist of 2 classes they were English 18A and B, the sample chosen by using purposive sampling technique where the sample was English 18A and the total number of the sample were 21 students. This research was conducted by using Pre-Experimental design with one group pre-test and post-test. The result of this research shows that T-test value was 14,89 and t-table value was 1,703. Based on the statistic analysis results it was found that T-value was higher than T-table. It can be concluded that application of tongue twister improves the students’ pronunciation skill of /ð/ and /θ/ sounds.